Dose Escalation Trial of Desulfated Heparin (ODSH) in Septic Peritonitis - Mauro, Katie D.; Lambert, Michele P.; Kowalska, M. Anna; Thawley, Vincent J.; Poncz, Mortimer; Otto, Cynthia M. (Frontiers in Veterinary Science, 2022)
Objective Septic peritonitis is associated with significant morbidity and mortality. As a potential therapeutic agent in the treatment of sepsis, 2-O, 3-O desulfated heparin (ODSH) reduces histones and platelet factor 4 (PF4) in mouse sepsis models. This pilot clinical trial evaluated the safety and effect of ODSH in client-owned dogs with septic peritonitis. Interventions In an IACUC-approved, open-label, prospective, dose-escalation clinical trial in 6 dogs with spontaneous septic peritonitis, ODSH administration was initiated following surgical explore to achieve source control. Acute patient physiology and laboratory evaluation (APPLEfast and APPLEfull) scores on admission, source of septic peritonitis, requirement for vasopressors, the administration of blood products, and survival to discharge were recorded. Platelet count, cell free DNA (cfDNA) concentration, and platelet factor 4 (PF4) concentrations were measured at the time of each ODSH dosage. A dose of ODSH was administered every 8 hs for a total of 4 doses (maximum total dosage 75 mg/kg) based on a pre-determined escalation protocol. Patients were monitored in the ICU following administration for evidence of clinical hemorrhage. Main Results The mean APPLEfast and APPLEfull scores on admission were 22 +/- 6 and 32 +/-10, respectively. Four dogs received 4 total dosages of ODSH and 2 dogs received 3 total dosages of ODSH intravenously. The mean total dosage of ODSH administered during the study period was 48.3 +/- 21.6 mg/kg. No dog required dose de-escalation or had any evidence of bleeding. Four dogs survived to discharge. Conclusions No adverse effects of ODSH administration were documented in dogs with septic peritonitis. A randomized controlled trial is necessary to evaluate ODSH as a novel therapeutic in the treatment of septic peritonitis.